Geophysical And Geotechnical Investigation Of The Effect Of Blasting And Open Cast Mining On Worked-out Underground Mines And Modes Of Failure Of These Workings - Fourie, Andries Benjamin (My University, 2015)
To make the method of coalmining known as 'strip-mining' economically viable extremely large amounts of explosive need co be detonated in any one particular blast. This is to ensure enough rock is broken co keep the large earthmoving machinery, used in this type of mining, productive. This type of coal-mining operation was undertaken at Rieespruit Opencast Colliery in the Eastern Transvaal. Adjacent to this colliery is an exiting underground coalmine, and it was feared that the large amount of energy released by the surface blasting would be sufficient to damage the coal pillars. The investigation of the above problem formed the basis of this dissertation. Moving-coil seismometers were installed underground in what was considered^ a representative pillar, and continuous records of ground particle motion due to blasting were obtained from these instruments. Further field instrumentation consist of tape-recording decks and electronic packages to amplify and record the seismic signals was located on surface in an instrument hut built specifically for this purpose. The object of obtaining the above records was to establish damage criteria, whereby change weight could be estimated, for given distances from the blast to the underground workings, which would not cause appreciable damage underground. Propagation laws were established relating peak particle velocity, which is widely used as an indicator of possible damage, to the distance from the blast and either the square root or cube-root of the maximum charge weight per delay. These results are presented graphically and could be used to determine allowable charge weights to ensure a certain particle velocity is not exceeded.